Beneficial effects of ginger on prevention of obesity through Modulation of gut microbiota - Negar Ghashghaei; Asma Rashki Kemmak; Elham Goli; Shima Shishebor Astaneh; Monir Dahri; Mohammad Reza Mazaheri Habibi (Journal of Health, Population and Nutrition)
Abstract Background The human gut microbiota performs a variety of essential physiological homeostasis functions, including the development of the immune system, nutrient synthesis, vitamin production, and energy metabolism. Ginger's extensive pharmacological actions include anti-inflammatory, antioxidant, hypoglycemic, and lipid-lowering effects. This study aimed to investigate the beneficial effects of ginger on the prevention of obesity through the modulation of gut microbiota. Methods This study was carried out as a systematic review in 2024 by searching on the reliable databases of PubMed, Web of Sciences, and Scopus using the keywords "Obesity", "Gut-Microbiota", "Ginger" and their MeSH were analyzed with no time limit. Articles published in English that specifically focused on the beneficial effects of ginger in the prevention of obesity through the modulation of gut microbiota were included. Abstracts, letters to the editor, protocols, review articles and studies were inaccessible were excluded from consideration. To assess the quality of the included studies, a tool comprising 10 items was developed. Findings Generally, 3192 papers were retrieved from the above-mentioned databases and nine papers were considered for the present study after reading titles and abstracts and by considering the inclusion and exclusion criteria. In all these studies, the impact of ginger on gut microbiota has been examined, with a consistent focus on its effects on obesity. Overall, the existing evidence suggests that ginger not only positively influences gut microbiota but also serves as an effective agent in the prevention and management of obesity. Conclusion These findings highlight the potential of ginger as a natural and effective option in obesity management programs and for improving overall health. Nonetheless, it is clear that the amount of ginger ingested may influence its effects, and more research is required to establish the proper dosage and understand the exact how ginger supplementation works.